ANALISIS ETIKA BISNIS ISLAM TERHADAP USAHA KULINER DI KABUPATEN BIREUEN - Zahari (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2023)
This research investigates culinary business practices in Bireuen, emphasizing the concepts of halal, food safety, and the formalities hindering Micro, Small, and Medium Enterprises (MSMEs). The findings reveal a high awareness among business owners regarding Islamic business ethics and food safety. However, formalities such as obtaining permits from the National Agency of Drug and Food Control (BPOM) and halal certification from the Indonesian Ulema Council (MUI) pose challenges, particularly for MSMEs with limited capital. Respondents express a strong intention to enhance the quality and halal status of their food products. The research results underscore the need for government involvement in providing financial support and guidance to foster sustainable growth in the culinary industry while adhering to Islamic business ethics standards.